Evaluating training programs : the four levels - Kirkpatrick, Donald L. (Berret-Koehler Pub. San FranciscoUS, 1998)
Describes concepts, guidelines, principles and techniques for understanding and implementing each of the four levels of the model for evaluating training programmes. Includes guidelines for evaluating reaction, learning, behaviour, and results. Provides case studies which demonstrate how various organizations have used the evaluation strategy.